1999
DOI: 10.1021/jf990029q
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Fractionation of Grape Proanthocyanidins According to Their Degree of Polymerization

Abstract: A method was developed for the fractionation of grape (seed or skin) proanthocyanidins according to their degree of polymerization. After precipitation in chloroform/methanol (75:25, v/v), the grape proanthocyanidins were deposited onto an inert glass powder column and sequentially dissolved in several fractions by increasing proportions of methanol in the solvent. Each fraction from each proanthocyanidin source was quantified and characterized after acidic degradation with phenylmethanethiol (i.e., thiolysis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
134
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(164 citation statements)
references
References 26 publications
29
134
0
1
Order By: Relevance
“…Reductions in blood glucose levels were statistically significant between the control curve and test curves at all time intervals. In similar experiments a higher dose of 150mg/kg of the ethylacetate fraction had resulted in a 36.9% reduction in blood glucose at 2 hr post glucose administration [28].…”
Section: Effects On Glucose Tolerancementioning
confidence: 80%
See 3 more Smart Citations
“…Reductions in blood glucose levels were statistically significant between the control curve and test curves at all time intervals. In similar experiments a higher dose of 150mg/kg of the ethylacetate fraction had resulted in a 36.9% reduction in blood glucose at 2 hr post glucose administration [28].…”
Section: Effects On Glucose Tolerancementioning
confidence: 80%
“…An in vivo study using Sprague Dawley rats carried out by Fernando and Thabrew [58] has demonstrated that an aqueous extract of mature leaves of A. heterophyllus exerted no adverse effects even after daily administration for 30 days, as assessed by effects on (a) liver function, (b) haematological parameters such as haemoglobin concentration, red blood cell count, white blood cell count and packed cell volume, (c) reproductive ability of experimental animals and (d) histology of body organs (heart, liver, lung,kidney, intestine and pancreas). Investigations carried out by Chandrika et al [28] also have revealed that the chronic administration of the ethylacetate fraction of A. heterophyllus leaves to normoglycaemic rats over a period of twelve weeks at a dose of 50 mg/kg body weight failed to bring any overt signs of toxicity such as salivation, diarrhea, lacrymation, postural abnormalities or behavioural changes. No significant differences had been observed in the liver function tests and the histology of various body organs between the test and the control groups.…”
Section: Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…11) Whereas, the proanthocyanidin in grape seed is procyanidin type and represents major oligomer with DP4 (60%). 17) Based on Sephadex LH gel filtration column chromatography, the PRFR was co-eluted at the same fractions (fraction numbers 27 to 29) as the proanthocyanidin from grape seed extract as shown in the supplement data 1. Therefore, we propose that the majority of proanthocyanidin in the PRFR are the oligomer with the same DP of proanthocyanidin found in the grape seed extract as the structure was proposed in Fig.…”
Section: Discussionmentioning
confidence: 99%